Digital and intermedial literacy in literary reading: didactic guidelines for a reading mediation that integrates different artistic languages: (Palíndromo, 2024)
This paper reflects on how digital environments are transforming 21st century literature. We analyze the basic changes in literary production and reception in virtual and online environments, focusing on intermediality: the hybridization of artistic languages in synchronic and diachronic modes, especially the symbiosis of visual and verbal-literary language. We consider the reasons why these transformations, already well established in society and among children and young readers, keep on being neglected in Primary and Secondary Education and if they require specific interpretative strategies. Based on these reflections, we propose a referential didactic model for reading mediators, to approach intermedial (literary and visual) phenomena with a critical and dialogic approach.
Keywords: transmediality; intermediality; digital literature; reading mediation; critical reasoning